An Evidence-Based Practice Developed in-situ: Let's Talk About Children and a Consolidation of Its Evidence Base - Allchin, Becca; Solantaus, Tytti (Frontiers in Psychiatry, 2022)
Background: Traditional models of evidence-based practice assume knowledge is developed in research settings before being installed in practice settings. The role practice settings can play in enhancing effectiveness and enabling sustainability is not therefore acknowledged. Developing interventions in-situ alongside developing their evidence base, provides another pathway to evidence-based practice. One example is Let’s Talk about Children (LTC), a brief family-focused intervention that promotes parent, family and child wellbeing. Let’s Talk about Children has been developed and adapted to respond to the context into which it has been established, leading to different descriptions reported in its 20year collection of evidence. Collating the diverse literature on LTC, this paper showcases an evidence-based practice developed in-situ in order to guide future innovation. Method: Using an integrative review, key literature using LTC were identified through electronic databases and snowballing techniques. Constant comparison analysis synthesized the data to develop patterns and themes. Findings: From the 26 records, three forms of LTC were identified and outcomes related to parents, family and child wellbeing, implementation and sustainability were collated. Consolidated outcomes show overall agreement in effectiveness and acceptability outcomes across different settings and populations. Implementation and sustainability impacts are entwined with the context, and influenced by its development in-situ. Conclusions: The study documents that the in-situ model is effective at developing sustainable evidence-based practice. In consolidating the evidence, the review clarified LTC’s forms and outcomes, and draws attention to the importance of research on mechanisms of change.